Electrical synapses and the development of inhibitory circuits in the thalamus - Zolnik, Timothy A. (J Physiol, 2016)
KEY POINTS: The thalamus is a structure critical for information processing and transfer to the cortex. Thalamic reticular neurons are inhibitory cells interconnected by electrical synapses, most of which require the gap junction protein connexin36 (Cx36). We investigated whether electrical synapses play a role in the maturation of thalamic networks by studying neurons in mice with and without Cx36. When Cx36 was deleted, inhibitory synapses were more numerous, although both divergent inhibitory connectivity and dendritic complexity were reduced. Surprisingly, we observed non‐Cx36‐dependent electrical synapses with unusual biophysical properties interconnecting some reticular neurons in mice lacking Cx36. The results of the present study suggest an important role for Cx36‐dependent electrical synapses in the development of thalamic circuits. ABSTRACT: Neurons within the mature thalamic reticular nucleus (TRN) powerfully inhibit ventrobasal (VB) thalamic relay neurons via GABAergic synapses. TRN neurons are also coupled to one another by electrical synapses that depend strongly on the gap junction protein connexin36 (Cx36). Electrical synapses in the TRN precede the postnatal development of TRN‐to‐VB inhibition. We investigated how the deletion of Cx36 affects the maturation of TRN and VB neurons, electrical coupling and GABAergic synapses by studying wild‐type (WT) and Cx36 knockout (KO) mice. The incidence and strength of electrical coupling in TRN was sharply reduced, but not abolished, in KO mice. Surprisingly, electrical synapses between Cx36‐KO neurons had faster voltage‐dependent decay kinetics and conductance asymmetry (rectification) than did electrical synapses between WT neurons. The properties of TRN‐mediated inhibition in VB also depended on the Cx36 genotype. Deletion of Cx36 increased the frequency and shifted the amplitude distributions of miniature IPSCs, whereas the paired‐pulse ratio of evoked IPSCs was unaffected, suggesting that the absence of Cx36 led to an increase in GABAergic synaptic contacts. VB neurons from Cx36‐KO mice also tended to have simpler dendritic trees and fewer divergent inputs from the TRN compared to WT cells. The findings obtained in the present study suggest that proper development of thalamic inhibitory circuitry, neuronal morphology, TRN cell function and electrical coupling requires Cx36. In the absence of Cx36, some TRN neurons express asymmetric electrical coupling mediated by other unidentified connexin subtypes.